5-Aza Exposure Improves Reprogramming Process Through Embryoid Body Formation in Human Gingival Stem Cells - Diomede, Francesca; Zini, Nicoletta; Pizzicannella, Jacopo; Merciaro, Ilaria; Pizzicannella, Giuseppe; D’Orazio, Monica; Piattelli, Adriano; Trubiani, Oriana (Frontiers in Genetics, 2018)
Embryoid bodies (EBs) are three-dimensional aggregates formed by pluripotent stem cells, including embryonic stem cells and induced pluripotent stem cells. They are used as an in vitro model to evaluate early extraembryonic tissue formation and differentiation process. In the adult organisms, cell differentiation is controlled and realized through the epigenetic regulation of gene expression, which consists of various mechanisms including DNA methylation. One demethylating agent is represented by 5-Azacytidine (5-Aza), considered able to induce epigenetic changes through gene derepression. Human Gingival Mesenchymal Stem Cells (hGMSCs), an easily accessible stem cells population, migrated from neural crest. They are particularly apt as an in vitro study model in regenerative medicine and in systemic diseases.. The ability of 5-Aza treatment to induce hGMSCs toward a dedifferentiation stage and in particular versus EBs formation was investigated. For this purpose hGMSCs were treated for 48h with 5-Aza (5µM). After treatment, hGMSCs are organized as roundish 3D structures (EBs-hGMSCs). At light and transmission electron microscopy the cells at the periphery of EBs-hGMSCs appear elongated, while ribbon-shaped cells and smaller cells with irregular shape surrounded by extracellular matrix were present in the centre. By RT-PCR, EBs-hGMSCs expressed specific transcription markers related to the three germ layers as: MAP-2, PAX-6 (ectoderm), MSX-1, Flk-1 (mesoderm), GATA-4, GATA-6 (endoderm). Moreover, in EB-hGMSCs the overexpression of DNMT1 and ACH3 other than the down regulation of p21 was detectable. Immunofluorescence staining also showed a positivity for specific etodermal and mesodermal markers. In conclusion, 5-Aza was able to induce the direct conversion of adult hGMSCs into cells of three embryonic lineages: endoderm, ectoderm and mesoderm, suggesting their possible application in autologous cell therapy for clinical organ repair.